Ocular aberrations in keratoconus - V.V. Averich; G.B. Egorova (РМЖ "Клиническая офтальмология")
V.V. Averich, G.B. Egorova Research Institute of Eye Diseases, Moscow, Russian Federation The review presents the basic concepts of the wavefront, ocular aberrations and their changes in keratoconus (KC) — the most common form of primary ectatic corneal disorder. It also considers the issues of the posterior corneal surface impact on the indicators of general astigmatism and the wavefront. The authors note that a possible reason for the increase in the aberration level in KC are concomitant signs of dry eye syndrome (DYS). Adding that, the review also discusses methods for correcting aberrations in KC. To date, contact lens vision correction with rigid gas permeable lenses remains the most effective method of visual rehabilitation. The prescription with a combination of artificial tears and reparative medicine allows to almost completely neutralize the phenomena of keratomalacia (conjunctival xerosis). If a patient with KC has initial signs of DYS, it is advisable to use preservative-free low-viscosity artificial tears based on hyaluronic acid of various concentrations. If the patient uses contact lens vision correction to prevent hypoxia complications, it is justified to prescribe the antioxidant agent, methylethylpiridinol, which has an antiaggregational and antihypoxic effect. Keywords: keratoconus, ocular aberrations, posterior corneal surface, wavefront, Zernike polynomials, dry eye syndrome, antioxidant. For citation: Averich V.V., Egorova G.B. Ocular aberrations in keratoconus. Russian Journal of Clinical Ophthalmology. 2022;22(3):168–174 (in Russ.). DOI: 10.32364/2311-7729-2022-22-3-168-174.